Can ambient temperature patterns predict fireweed phenology? - Chaimungkhun Johansson, Jennifer (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2021)
The Earth’s climate has been changing with greater intensity and frequency in recent years. These changes, especially the warmer climate, have advanced plant phenology, thus increasing the risk of interspecific temporal mismatches, for example pollinators and pollinated flower species. This study’s aim is to find out if temperature accumulations can be used to predict Chamaenerion angustifolium flowering phenology. A novel short-term camera trap dataset and a 13-year old long-term dataset of C. angustifolium flowering were used in conjunction with air temperature from an ensemble dataset to calculate accumulated growing degree-days. A comparison between the short- and long-term dataset was required in case the two datasets wouldn’t provide similar result. A Mann-Whitney U-test suggested that there was no significant difference between the two methods of collecting flowering phenology data. A significant difference was provided by the Welch’s t-test in accumulated growing degree-days between flowering and non-flowering sites, which suggests that temperature accumulation could be used to predict flowering phenology of C. angustifolium.